Relating structural phase transitions to mechanoluminescence: The case of the Ca1−xSrxAl2Si2O8:1%Eu2+, 1%Pr3+ anorthite. (15th January 2020) - Feng, Ang; Michels, Simon; Lamberti, Alfredo; Van Paepegem, Wim; Smet, Philippe F.
Graphical abstract: Abstract: The phenomenon of mechanoluminescence (ML), where phosphors emit light when pressure is applied, is considered to be closely related to the crystallographic structure of those phosphors. In this work we unravel this connection for the anorthite solid solution Ca 1 − x Sr x Al2 Si2 O8, which displays two important phase transitions as a function of strontium content x (denoted as xSr ), i.e., the nearly second-order P 1 ¯ -I 1 ¯ transition and the ferroelastic I 1 ¯ -I 2 c transition at ambient temperature and pressure. The spontaneous strains reveal that the ferroelastic transition takes place when xSr ∈ (0.70, 0.75), while other optical methods suggest that the second-order P 1 ¯ − I 1 ¯ transition takes place when xSr is around 0.4. The ML intensity reaches its maximum when the second order transition takes place and drops to zero when the phosphors undergo the ferroelastic transition. The first transition already brings significant changes to electron occupations at traps in this solid solution. The structural phase transitions in the anorthite solid solutions are reflected in specific ML properties, such as the ML intensity and the load threshold. Further analysis suggests this is due to the structural change of the hosts and the trap properties (trap density and electron population function). Analysis of the ML dynamics may therefore serve as a useful tool to investigate phase transitions in ML phosphors.